2013
DOI: 10.7326/0003-4819-159-4-201308200-00005
|View full text |Cite
|
Sign up to set email alerts
|

A Home-Based Intervention to Reduce Depressive Symptoms and Improve Quality of Life in Older African Americans

Abstract: Background Effective care models for treating older African Americans with depressive symptoms are needed. Objective To determine whether a home-based intervention alleviates depressive symptoms and improves quality of life in older African Americans. Design Parallel, randomized trial stratified by recruitment site. Interviewers assessing outcomes were blinded to treatment assignment. (ClinicalTrials.gov: NCT00511680) Setting A senior center and participants’ homes from 2008 to 2010. Patients African A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(77 citation statements)
references
References 51 publications
2
73
0
1
Order By: Relevance
“…We examined whether the effects of four factors, depression knowledge/efficacy in symptom recognition, anxiety, behavioral activation, and formal service use mediated the relationship between intervention participation and the impact on depressive symptoms as measured by two indicators. Similar to our previous report involving the entire sample (Gitlin et al, 2013), results of these analyses confirmed that BTB had significant positive effects on depressive symptoms, and on three of four mediators. BTB reduced anxiety, and enhanced depression knowledge/symptom recognition and behavioral activation, all important outcomes for this group of older adults.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We examined whether the effects of four factors, depression knowledge/efficacy in symptom recognition, anxiety, behavioral activation, and formal service use mediated the relationship between intervention participation and the impact on depressive symptoms as measured by two indicators. Similar to our previous report involving the entire sample (Gitlin et al, 2013), results of these analyses confirmed that BTB had significant positive effects on depressive symptoms, and on three of four mediators. BTB reduced anxiety, and enhanced depression knowledge/symptom recognition and behavioral activation, all important outcomes for this group of older adults.…”
Section: Discussionsupporting
confidence: 88%
“…Following treatment, control group participants demonstrated benefits (4 to 8-months) similar in magnitude to the adjusted treatment effects for BTB participants in the first 4-months; and the initial BTB group maintained 4-month benefits at 8-months (Gitlin et al, 2013). …”
Section: Introductionmentioning
confidence: 82%
“…Additionally, at 4 months, 44% of BTB participants were in remission compared with 27% of wait-listed controls. 27 …”
Section: Methodsmentioning
confidence: 99%
“…Following the four-month multi-component, home-based intervention, participants in the intervention group were more likely than controls to enter remission. They also demonstrated clinical meaningful reductions in depression severity, as well as improved mood, quality of life, and depression knowledge (Gitlin et al, 2013). From development of the intervention through connecting with a difficult to reach target group for intervention delivery, community-engaged research methods were crucial to Beat the Blues’ success.…”
Section: Community-engaged Researchmentioning
confidence: 99%